Cultivating conscientious tourism caretakers: a phenomenographic continuum towards stronger sustainability. Issue 8 (17th April 2020) - Cotterell, Debbie; Ferreira, Jo-Anne; Hales, Rob; Arcodia, Charles
ABSTRACT: Despite attempts to improve the 'tourism curriculum space' in order to empower philosophic practitioners who are capable of thinking systemically and holistically about complex phenomenon such as sustainability, tourism curricula is still designed around less complex and weak conceptualizations of sustainability. The aim of this study is to uncover the range of qualitatively different ways of experiencing sustainability in a tourism context with the intent of forming a continuum that could serve as a useful teaching and learning strategy in developing more complex and 'stronger' conceptualizations of sustainability. Phenomenographic interviews with lecturers, students and industry workers revealed four qualitatively different ways of experiencing sustainability ranging from weak to very strong understandings of sustainability. The key outcome of this study is a practical continuum designed to (1) promote reflection within tourism educators on the conceptualizations underpinning their course design; as well as provide (2) a powerful teaching and learning tool designed to help higher education practitioners engage students with a broader and more varied range of understandings about the complex phenomenon that is sustainability. By introducing variation theory as an additional conceptual framework for explaining individuals' understandings of sustainability, this study makes a theoretical contribution to the field of tourism studies.